2007
DOI: 10.1111/j.1471-3802.2007.00080.x
|View full text |Cite
|
Sign up to set email alerts
|

Student researchers in the middle: using visual images to make sense of inclusive education

Abstract: Using ‘visual narrative’ theoretically and practically, this paper explores issues of inclusive education, during a period of curriculum reform and renewal in Australia. In Australia, the middle years of schooling, Years 5 to 9, are well researched and known as a period when students disengage with learning and participation in schooling. Research in the middle years affirms the importance of engaging with ‘student voice’. In this special edition, we are aiming to highlight how the use of visual imagery can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 15 publications
0
18
0
2
Order By: Relevance
“…At the same time, the fact that the production of the images and related comments has been guided by children is beneficial for them as they may be reassured that their views about their education are being listened to (Children and Families Act, 2014) and they are able to utilise whichever of their visual as well as verbal communication skills they are most comfortable with when explaining their experiences. This view is supported by Moss et al (2007) who also adopt visual methodologies when working with similarly aged primary children in Australia. Moss et al (2007:47) describe visual narrative methodologies as liberatory and empowering; as a way for young pupils to express their knowledge of education, and "give an authentic voice to their concerns and experiences regarding schooling".…”
Section: Accessing Perspectives Respecting Differing Voicesmentioning
confidence: 90%
“…At the same time, the fact that the production of the images and related comments has been guided by children is beneficial for them as they may be reassured that their views about their education are being listened to (Children and Families Act, 2014) and they are able to utilise whichever of their visual as well as verbal communication skills they are most comfortable with when explaining their experiences. This view is supported by Moss et al (2007) who also adopt visual methodologies when working with similarly aged primary children in Australia. Moss et al (2007:47) describe visual narrative methodologies as liberatory and empowering; as a way for young pupils to express their knowledge of education, and "give an authentic voice to their concerns and experiences regarding schooling".…”
Section: Accessing Perspectives Respecting Differing Voicesmentioning
confidence: 90%
“…La dinámica Diamond-9 es una estrategia enmarcada en la investigación visual siendo reconocida por su valor para implicar a los alumnos en el proceso investigador al invitarles a reflexionar sobre sus ideas y sentimientos (Moss, Deppeler, Astley, y Pattison, 2007;Niemi, Kumpulainen y Lipponen, 2015;Rose, 2012;Thomson, 2009). …”
Section: Instrumentosunclassified
“…They found that students felt included in the community when their concerns were acknowledged and acted upon. Moss, Deppeler, Astley, and Pattison (2007) used the methodology of visual narrative to document marginalised students' perceptions of their school environment. In the present study, students gave voice to their personal experiences of school.…”
Section: Student Voicesmentioning
confidence: 99%